The effectiveness of the project-based learning model assisted by audio visual media in writing opinion texts in vocational schools - Susilo, Jimat; Kusmana, Suherli; Anggraeini, Reni (Universitas Ahmad Dahlan, 2024)
Learning to write opinion texts is very required in the Vocational Curriculum However, students still have many difficulties in writing opinion texts. This research aims to overcome the problem of writing opinion texts in vocational schools through a Project Based Learning model assisted by audio-visual media. The object of the research was carried out at SMK Budi Tresna Muhamadiyah Cirebon grade XII. The research method, through experiments, tests the effectiveness of the Project Based Learning model in improving students' ability to write opinion article texts. The research instrument is in the form of a test to collect data on students' ability to write opinion article texts with the help of audio-visual media. The test data is in the form of text of opinion articles written by students both through prates and post-tests. The results showed that learning in the experimental class using the Project Based Learning model got a score of 1790 with an average score of 89.5 higher than the control class using the contextual model got a score of 1340 with an average score of 67. In addition, the results of significant tests that have been carried out by the experimental class (KE) > the control class (KK), H0 is rejected and H1 is accepted, then the VAK Project Based Learning model is declared effective. Based on the calculation of the significance test results, a calculation of 3,515 was obtained at a significant level of 5% and a table of 1,687. This shows that H1 is accepted and H0 is rejected. Thus, applying the Project Based Learning model to write opinion article texts for grade XII students of SMK Budi Tresna Muhammadiyah Cirebon for the 2024/2025 school year is effective.